The happy families of social learning – mapping the complex domains of learning and social change - Le Borgne, Ewen; Jackson, Carl; Schuetz, Tonya; Förch, Wiebke; Cranston, Pete (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2014)
Various broad fields are connected with social learning and are effectively playing as related families. This Learning Brief outlines research fields related to social learning.